Pelestarian Nilai-Nilai Budaya Minangkabau Melalui Kegiatan Ekstrakurikuler Sekolah Menengah Pertama - Syahriani, Syahriani; Dirsa, Andika (Tarikhuna: Journal of History and History Education, 2023)
This research was motivated by the cause of juvenile delinquency in SMP Negeri 24 Padang is that not a few junior high school students in adolescence experience deviation by being disrespectful to teachers, saying, rude, not collecting assignments, and skipping classes and climbing fences some students, especially men, are caught smoking in the school environment. Therefore, it is proven as a form of concern for the development of the younger generation, and the increasingly shifting culture in people's lives. Sekolah Menengah Junior (SMP) Negeri 24 Padang is building a "Cultural Gallery". This is done as a means of awakening the stem of tarandam nan lamo dikana juo through extracurricular students of State Junior High School (SMP) 24 Padang.This study aims to: (1) Know the journey of Minangkabau Cultural Values in State Junior High School (SMP) 24 Padang. (2) Knowing the preservation of Minangkabau cultural values through extracurricular activities at SMP Negeri 24 Padang. (3) Knowing the obstacles faced in the preservation of Minangkabau culture in State Junior High School (SMP) 24 Padang. This research method uses qualitative research, data sources are principals, teachers, and learners. This study used data collection techniques in the form of observation, interviews, and documentation.Based on the results of this study, namely the preservation of Minangkabau cultural values through extracurricular activities at State Junior High School (SMP) 24 Padang. The learning process in class and outside the classroom includes extracurricular activities such as silat and traditional dances, Minangkabau pantun competitions, and Minang corners as well as programs to wear basiba clothes and use Minang language every Thursday.